The Free Market and the Moarl Limits - MakarovKirill (Journal of Economic Sociology, 2015)
Modern society, in which it is possible to buy or sell most goods, is regarded as far more rationally arranged comparing to those where goods distribution is grounded on the principle of reallocation or of reciprocity. Indeed there is rationale for considering that a market, if not hindered by other forces, will distribute goods effectively, providing to those who are able and willing to pay for them. However the question is: does this lead to a welfare state? Or does it cause social atomization, inequality of growth and a predominance of economic calculation? Commodification is a process that is registered through the whole history of capitalism’s development. Although it may be regarded as a natural market attribute, commodification should be permanently examined with thoroughness and never neglected. Allowed out of control, commodification may lead to an unexpected aftermath, reshaping the image of society in an undesirable way. Pricing goods does not change their functionality but it surely alters the meaning that commodity might have attached to it. Michael Sandel’s new book, “What Money Can’t Buy: The Moral Limits of Markets” is all about the destructive outcomes of an uncontrolled commodification process.